2019
DOI: 10.20531/tfb.2019.47.1.08
|View full text |Cite
|
Sign up to set email alerts
|

Five new species of Henckelia (Gesneriaceae) from Myanmar and Thailand

Abstract: Five new species of Henckelia are described, two from Myanmar: Henckelia campanuliflora and H. candida, and the others from Thailand: H. amplexifolia, H. nakianensis and H. dasycalyx. A key to the 1 to 2-leaved species of the genus is given, as well as photographs, ecology, and also IUCN conservation status for the new species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 4 publications
1
13
0
Order By: Relevance
“…During our field investigation in southeastern Yunnan in 2016, several unusual species of Gesneriaceae caught our attention. After careful study of relevant specimens and taxonomic publications from the adjacent regions (Wang et al 1990, 1998; Li and Zhu 2010; Weber et al 2011; Middleton et al 2013; Möller et al 2016; Xu et al 2017; Sirimongkol et al 2019), we concluded that these plants represent two new members of Henckelia . Descriptions and illustrations of the new species are presented here; the morphological characters are also compared with those of closely related species.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…During our field investigation in southeastern Yunnan in 2016, several unusual species of Gesneriaceae caught our attention. After careful study of relevant specimens and taxonomic publications from the adjacent regions (Wang et al 1990, 1998; Li and Zhu 2010; Weber et al 2011; Middleton et al 2013; Möller et al 2016; Xu et al 2017; Sirimongkol et al 2019), we concluded that these plants represent two new members of Henckelia . Descriptions and illustrations of the new species are presented here; the morphological characters are also compared with those of closely related species.…”
Section: Introductionmentioning
confidence: 74%
“…and H. candida Sirim. (Sirimongkol et al 2019) were recorded from limestone areas. We believe that the habitat driven speciation is worthy of further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Petrocosmea has more than 50 known species distributed in China, Vietnam, Thailand and India (Han et al 2018b); Didymocarpus has approximately 70 species range from northwest India, eastwards through Nepal, Bhutan, northeast India, Myanmar, to southern China, Vietnam, Laos, Cambodia, Thailand, the Malay Peninsula and northwards to Sumatra (Weber and Burtt 1998; Weber et al 2000; Möller et al 2016a; Hong et al 2018); Henckelia has 64 known species found in Sri Lanka, southern and north-eastern India, Nepal, Bhutan, southern China, northern Laos, northern Vietnam and northern Thailand (Weber et al 2011; Sirimongkol et al 2019). After thorough comparisons of diagnostic morphological, anatomical features and herbarium specimens available at BM, E, HITBC, K, KUN, NYBG and P with similar taxa of Petrocosmea , Didymocarpus , and Henckelia , and consulting the relevant literature for Petrocosmea (Wang 1985; Wang et al 1990, 1998; Burtt 1998a; Li and Wang 2004; Wei and Wen 2009; Gou et al 2010; Middleton and Triboun 2010; Zhao and Shui 2010; Shaw 2011; Xu et al 2011; Qiu and Liu 2015; Qiu et al 2011, 2012, 2015a, 2015b; Wang et al 2013; Zhang et al 2013; Han et al 2017, 2018a, 2018b), Didymocarpus (Wang et al 1998; Burtt 1998b, 1999, 2001; Weber et al 2000; Hilliard 2001; Li and Wang 2004; Nangngam and Maxwell 2013; Wen et al 2013; Li and Li 2014; Nangngam and Middleton 2014; Phuong et al 2014; Li and Wang 2015; Cai et al 2016; Joe et al 2016; Hong et al 2018), and Henckelia (Wang et al 1998; Weber and Burtt 1998; Burtt 2001; Weber et al 2011; Middleton et al 2010; Ranasinghe et al 2016; Sirimongkol et al 2019) from China and adjacent regions, it was confirmed that the four specie...…”
Section: Introductionmentioning
confidence: 99%